An analysis on Free Convection Cooling of a 3x3 Heater Array in Rectangular Enclosure using Cu-EG-Water Nanofluid - Purusothaman, A.; Divya, V.; Nithyadevi, N.; Öztop, Hakan Fehmi (Isfahan Univ Technology, 2016)
This paper deals with the study of natural convection cooling of a discrete heater array in Cu-EG-water nanofluid filled rectangular enclosure. A 3 x 3 array of non-protruding heat sources is embedded on one of the vertical walls of the enclosure while the top horizontal and opposite vertical walls are assumed to be isothermally cold. The remaining portions in which the heaters are mounted and all other walls are insulated. The above setup is modeled into a system of partial differential equations which are solved numerically using finite volume method based on the Semi-Implicit Method for Pressure Linked Equation (SIMPLE) algorithm and power law scheme. The wide range of parameters for computation are the aspect ratio of the enclosure, the mixture proportion of Ethylene glycol-water, the solid volume fraction of the nanoparticle along with two different thermal conductivity models. It is observed that the proper choice of the computation parameters and thermal conductivity models could be able to maximize the heat transfer rate from the heater array. Also, the results obtained in this study will provide new guidelines in the field of electronic equipment cooling.
Keywords: Natural Convection; Equipment Cooling; Heater Array; Nanofluid; Thermal Conductivity